2020
DOI: 10.1080/13613324.2020.1842351
|View full text |Cite
|
Sign up to set email alerts
|

‘Oh, this is really great work—especially for a Turk’: a critical race theory analysis of Turkish Belgian students’ discrimination experiences

Abstract: Students of Turkish descent suffer various forms of discrimination in education in Flanders (the northern part of Belgium). Nevertheless, few studies have documented how these discrimination experiences are situated within structures of ethnic inequality in education. Adopting a critical race theory approach, experiences of Turkish Belgian university students were analysed to expose deficit assumptions towards ethnic minorities and push against inequity in education. The accounts of students show the exclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…Black students are also disproportionately more likely to leave their degree programme prior to completion (Higher Education Statistics Agency [HESA], 2018). These patterns of racial inequality are common across Western higher education systems including the US, Australia, Belgium, and France (e.g., Byrd, 2014; Colak, Van Praag, & Nicaies, 2020; Ichou & van Zanten, 2019; Pitman, Roberts, Bennett, & Richardson, 2019). Recently, student campaigns, media commentary, and academic voices have insisted that our attention shifts from encouraging underrepresented groups through the door, to addressing the Whiteness of our institutions that signals non‐belonging and may compromise Black students' ability to thrive (National Union of Students, 2011; Richardson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Black students are also disproportionately more likely to leave their degree programme prior to completion (Higher Education Statistics Agency [HESA], 2018). These patterns of racial inequality are common across Western higher education systems including the US, Australia, Belgium, and France (e.g., Byrd, 2014; Colak, Van Praag, & Nicaies, 2020; Ichou & van Zanten, 2019; Pitman, Roberts, Bennett, & Richardson, 2019). Recently, student campaigns, media commentary, and academic voices have insisted that our attention shifts from encouraging underrepresented groups through the door, to addressing the Whiteness of our institutions that signals non‐belonging and may compromise Black students' ability to thrive (National Union of Students, 2011; Richardson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, qualitative studies (Abu El-Haj, 2007;Rosenbloom & Way, 2004) have highlighted that ethnic minority students did not necessarily perceive any kind of conflict with teachers as examples of ethnic-racial discrimination. Instead, they perceived to be discriminated against when teachers did not respect or care about them as individuals or enacted subtle forms of discrimination, such as microaggressions (e.g., praising third-generation immigrant youth for their skills in the language of instruction) (Colak et al, 2020). In sum, TBRED can be conceptualized as differential treatment due to students' race or ethnicity but may manifest in different ways.…”
mentioning
confidence: 99%
“…Experiencing discrimination from teachers has been linked to lessened school engagement among ethnic minority youth in multiple European settings (Artamonova, 2018;D'hondt et al, 2016). Importantly, anti-immigrant and anti-Muslim sentiment are often intertwined (Reijerse et al, 2013), meaning, Muslim youth face heightened discrimination, including in educational settings (Colak et al, 2020;Welply, 2018). A nationally representative survey (N = 2012) in Germany found that nearly half of respondents agreed that, 'Islam does not belong in Germany' (Ahrens, 2018), reflecting societal anti-Muslim sentiment and behaviour, also known as Islamophobia (Kunst et al, 2013).…”
Section: Perceived Discrimination and Societal Islamophobiamentioning
confidence: 99%